Experience of the introduction of surgery with artificial circulation in the regional department of vascular surgery - Yu.S. Spirin (Кардіохірургія та інтервенційна кардіологія)
The aim – introduction of surgery with artificial circulation in the regional department of vascular surgery. Materials and methods. In 2010 department of vascular surgery, intensive care unit and laboratory of the Kherson regional hospital were completed with special medical equipment needed to perform procedures with artificial circulation. Vascular surgeons received certificate «Surgery of heart and main vessels». 24 master classes and 28 training courses in the leading Ukrainian cardiac surgery clinics were organized. 120 coronary anastomoses were performed on pig hearts. During 2010–2016 years 215 procedures with artificial circulation were performed. Results. Transformation of the vascular surgery department to the cardiovascular surgery was an optimal way of introduction of cardiac surgery considering features of the regional medicine in Ukraine. Organization of the master classes, training courses and coronary bypass surgery procedures on the pig hearts made possible to develop regional cardiac surgery without long-term interruption of the usual process and without influence upon quality of the work. Postoperative complication rate was 6.3% and mortality was 2.3 %. Conclusion. Introduction of the surgery with artificial circulation led to immediate positive results in 97.7 % of cases without negative influence upon existing system of the management of vascular pathology.